2021
DOI: 10.1093/glycob/cwab040
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 impacts on glucose homeostasis by modulating pancreatic insulin release

Abstract: Type-2 diabetes mellitus (T2DM) is an expanding global health problem, involving defective insulin secretion by pancreatic β-cells and peripheral insulin resistance, leading to impaired glucose regulation. Galectin-1, an endogenous lectin with affinity for N-acetyllactosamine (LacNAc)-containing glycans, has emerged as a regulator of inflammatory and metabolic disorders. However, the role of galectin-1 in glucose homeostasis and pancreatic β-cell function, independently of hypercaloric diets, has not been expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…However, residual CV risk persists and new approaches mainly focused on anti-inflammatory agents are being tested (45,46). In this regard, previous studies demonstrated the protective role of rGal-1 treatment in the resolution of acute and chronic inflammatory conditions (47), including AMI (11), autoimmune neuroinflammation (48), inflammatory bowel diseases (49), and diabetes (50,51). In this study, we investigated the role of Gal-1 as a novel therapeutic strategy in two different chronic diseases, such as atherosclerosis and AAA.…”
Section: Discussionmentioning
confidence: 99%
“…However, residual CV risk persists and new approaches mainly focused on anti-inflammatory agents are being tested (45,46). In this regard, previous studies demonstrated the protective role of rGal-1 treatment in the resolution of acute and chronic inflammatory conditions (47), including AMI (11), autoimmune neuroinflammation (48), inflammatory bowel diseases (49), and diabetes (50,51). In this study, we investigated the role of Gal-1 as a novel therapeutic strategy in two different chronic diseases, such as atherosclerosis and AAA.…”
Section: Discussionmentioning
confidence: 99%
“…( A ) Circulating galectin-1 levels are elevated in human obesity (~25% higher in obese vs. lean [ 64 ]) and in HFD-fed mice (~50% higher in HFD vs. chow [ 22 ]). ( B ) Circulating galectin-1 is positively associated with serum insulin levels in humans and modulated insulin secretion in mice [ 64 , 80 ]. Further, galectin-1 inversely associates with plasma glucose [ 64 ], but galectin-1 reduced glucose uptake in human adipose cells in vitro [ 15 ].…”
Section: Galectin-1 In the Adipose Tissue And In Obesitymentioning
confidence: 99%
“…Further, galectin-1 inversely associates with plasma glucose [ 64 ], but galectin-1 reduced glucose uptake in human adipose cells in vitro [ 15 ]. Insulin and glucose confer direct stimulatory effects on galectin-1 secretion to cell media from several cell types [ 71 , 77 , 80 , 94 , 95 , 96 ]. Galectin-1 is positively associated with circulating levels of IL-6, TNF-α and CRP [ 47 , 64 ].…”
Section: Galectin-1 In the Adipose Tissue And In Obesitymentioning
confidence: 99%
See 2 more Smart Citations